The Longitudinal Course of Prospectively Recorded Patient-reported Outcomes in Prostate Cancer Patients Treated with Surgery and Salvage Radiotherapy - Hjelle, Line Veronika; Sælen, Marie; Aarsæther, Erling Johan; Knutsen, Tore; Andersen, Sigve; Bentzen, Anne Gry; Richardsen, Elin; Wilsgaard, Tom; Fosså, Sophie Dorothea; Haugnes, Hege Sagstuen (European Urology Open Science, 2023)
Background - Patient-reported outcome measures (PROMs) after prostate cancer (PC) treatment, including both radical prostatectomy (RP) and salvage radiation therapy (SRT), are under-reported. Objective - To investigate PROMs longitudinally from before SRT until 18 mo after SRT for men treated with contemporary treatment modalities. Design, setting, and participants - This prospective, longitudinal cohort study included 120 men (whole cohort) treated with SRT administered with volumetric modulated arc radiotherapy from 2016 to 2021 at the University Hospital of North Norway. The whole cohort was followed from before SRT until 18 mo after SRT. A subcohort of 48 men was followed from before RP until 18 mo after SRT. Outcome measurements and statistical analysis - PROMs were collected with the Expanded Prostate Cancer Index-26 (EPIC-26), covering symptoms of urinary incontinence, urinary irritative, bowel, sexual, and hormonal domains. The domain scores were inquired before RP, 3 mo after RP, before SRT, at SRT termination, and 3 and 18 mo after SRT. We used linear mixed models with repeated measurements design to assess changes in PROMs throughout the treatment period. Results and limitations - The median age before SRT was 63 yr. For the whole cohort, all five domains worsened at 3 and 18 mo after SRT compared with those before SRT. The estimated mean changes from before SRT to 18 mo after SRT are as follows: urinary incontinence –13.1, urinary irritative function –10.4, bowel –16.8, sexual function –9.1, and hormonal function –20.2 (at clinically important levels for all domains but sexual). For the subcohort, the mean urinary incontinence, bowel, sexual, and hormonal functions were significantly worsened 3 and 18 mo after SRT compared with those before RP at clinically important levels. Conclusions - Men treated for PC report particular increased severity of urinary, bowel, sexual, and hormonal symptoms after SRT compared with baseline status.